1988
DOI: 10.1111/j.1365-2907.1988.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of tuberculosis in a naturally infected Badger population

Abstract: T h e dynamics of bovine tuberculosis infection in a wild Badger population have been studied since 1981. Faeces are sampled regularly to determine the distribution of infection in the study area. Badgers in known infected social groups, plus the neighbouring groups, are periodically caught and subjected to full clinical and bacteriological examination to monitor the progression of infection within and between groups of Badgers. The interim results of this study are presented and discussed. During 5 years (198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
104
3

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 12 publications
9
104
3
Order By: Relevance
“…A second objective, which commenced in earnest in 1981, was to study tuberculosis and its effects in a naturally infected badger population. Some of the findings of this study, which is still in progress, have been reported previously [3, [6][7][8][9].…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…A second objective, which commenced in earnest in 1981, was to study tuberculosis and its effects in a naturally infected badger population. Some of the findings of this study, which is still in progress, have been reported previously [3, [6][7][8][9].…”
Section: Introductionsupporting
confidence: 70%
“…The study area in Gloucestershire, covering an area in excess of 8 kM2, has been described in detail previously [6,9].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another likely reason for the failure of previous strategies is that for the culling-based strategies, lactating females have been released when captured (White & Harris 1995b). The extent of pseudo-vertical transmission in the epidemiology of the disease is unclear (Cheeseman et al 1981(Cheeseman et al , 1988White & Harris 1995a), but not culling lactating females could help to maintain the infection within the population. Fertility control would avoid the need for the release of lactating females on humane grounds.…”
Section: Introductionmentioning
confidence: 99%